Exploring Design Features in Mobile Shopping Applications: A Comprehensive Analysis and User-Centric Perspective - Karakurt, Necip Fazil; Arslan, Ozlem; Ecem, Ecem; Ilbahar, Esra; Cebi, Selcuk (OLD CITY PUBLISHING INC, 2026)
Despite significant resource allocation, mobile applications lacking effective design are phased out before gaining widespread adoption. To ensure the sustainability of mobile applications, a comprehensive analysis of customer expectations is imperative. This research aims to investigate user preferences regarding the features of mobile applications, drawing data from a survey conducted with 525 participants and incorporating 33 essential features for a mobile shopping application. The study employs the KANO model, Timko classification, and fuzzy Kano model to achieve two main objectives. Firstly, it seeks to compare results obtained from these classification methods, assessing the impact of mobile application features on user satisfaction and perceived quality. Secondly, the study analyzes classification outcomes for participant groups categorized by demographic factors such as gender, age, and marital status. The study's findings revealed that the identified 33 features are categorized into four groups, and no statistically significant differences were observed among any of these groups.
Keywords: User experience; kano model; timko model; fuzzy kano model; mobile applications design features; WEBSITE DESIGN; RELATIVE IMPORTANCE; WEB USABILITY; QUALITY; MODEL; AESTHETICS; PREFERENCE; Computer Science; Science & Technology - Other Topics